Infection by CagA‐Positive Helicobacter pylori Strains and Bone Fragility: A Prospective Cohort Study. (31st August 2020) - Gennari, Luigi; Merlotti, Daniela; Figura, Natale; Mingiano, Christian; Franci, Maria Beatrice; Lucani, Barbara; Picchioni, Tommaso; Alessandri, Mario; Campagna, Maria Stella; Gonnelli, Sara; Bianciardi, Simone; Materozzi, Maria; et al.
ABSTRACT: Helicobacter pylori (HP) infection is a common and persistent disorder acting as a major cofactor for the development of upper gastrointestinal diseases and several extraintestinal disorders including osteoporosis. However, no prospective study assessed the effects of HP on bone health and fracture risk. We performed a HP screening in a population‐based cohort of 1149 adults followed prospectively for up to 11 years. The presence of HP infection was assessed by serologic testing for serum antibodies to HP and the cytotoxin associated gene‐A (CagA). The prevalence of HP infection did not differ among individuals with normal bone mineral density (BMD), osteoporosis, and osteopenia. However, HP infection by CagA‐positive strains was significantly increased in osteoporotic (30%) and osteopenic (26%) patients respect to subjects with normal BMD (21%). Moreover, anti‐CagA antibody levels were significantly and negatively associated with lumbar and femoral BMD. Consistent with these associations, patients affected by CagA‐positive strains had a more than fivefold increased risk to sustain a clinical vertebral fracture (HR 5.27; 95% CI, 2.23–12.63; p < .0001) and a double risk to sustain a nonvertebral incident fracture (HR 2.09; 95% CI, 1.27–2.46; p < .005). Reduced estrogen and ghrelin levels, together with an impaired bone turnover balance after the meal were also observed in carriers of CagA‐positive HP infection. HP infection by strains expressing CagA may be considered a risk factor for osteoporosis and fractures. Further studies are required to clarify in more detail the underlying pathogenetic mechanisms of this association. © 2020 American Society for Bone and Mineral Research (ASBMR).